Knowledge Of Breast Cancer Prevention And 'Cerdik' Behavior In Adult Women In Tlogomas Malang - Ronasari Mahaji Putri; Wahidyanti Rahayu Hastutiningtyas (Universitas Tribhuwana Tunggadewi, 2025)
The incidence of breast cancer continues to rise and constitutes a significant global health issue, including in Indonesia. Early detection of breast cancer, although seemingly simple, is often neglected by women. This study aims to assess knowledge regarding breast cancer prevention and its correlation with the â€œCERDIKâ€ behavior among adults. The research design is non-experimental with a cross-sectional approach. The population comprises all adults in the Tlogomas area, with a sample of 81 individuals selected through accidental sampling. The independent variable is knowledge of breast cancer prevention, while the dependent variable is the